EMPOWERING LEMPANGANG VILLAGE YOUTH THROUGH THE LEMPANGANG ENGLISH CLUB PROGRAMME - Al Ayyubi, Ibnu Imam; Nurhikmah; Noerzanah, Firda; Prilian, Rismayanti; Oktavia, Puji Asiani; Ilmi, Aziz Nurul; Fadilah, Risa Alfina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Youth empowerment in rural areas plays a crucial role in developing the potential and skills of the younger generation to contribute to the progress of society. Lempangang Village, located in Gowa Regency, has great potential to improve the quality of life for its residents, especially the youth, which can be maximized through empowerment programs. One such program designed by the Lempangang Youth Organization (Karang Taruna) to enhance the skills and abilities of the village's youth is the Lempangang English Club (LEC), which aims to improve the youth's English language skills through fun and interactive learning activities. This study aims to analyze the implementation and impact of the LEC program on youth empowerment in Lempangang Village. Using a qualitative approach and case study method, the research gathered data through interviews, observations, and documentation of activities conducted by LEC members. The results show that the LEC program not only enhances the English proficiency of elementary, middle, and high school participants, but also has a positive impact on their self-confidence, social skills, and preparedness for entering the workforce. The program also encourages youth to become more active in social and community activities, thus increasing their role in village development. However, there are challenges faced, such as limited facilities and resources, which need to be addressed to maximize the program’s impact. Therefore, this study recommends strengthening supporting infrastructure, increasing stakeholder involvement, and expanding the program to other villages as part of a broader youth empowerment effort.